Optimization of Logistics and Industrial Wastewater Treatment System Using Grey Wolf Optimization Algorithm - Mahmoodabadi, Mostafa; Abedi, Sadegh; Danesh Shakib, Masoumeh (Management Strategies and Engineering Sciences, 2024)
Industrial wastewater collection involves the systematic gathering, transportation, and disposal of waste generated by industrial activities. This process is crucial for maintaining environmental health and safety, as industrial wastewater may contain hazardous materials that require special management. Effective waste collection strategies not only help reduce pollution but also contribute to the recycling and reuse of materials, thereby conserving resources. Advanced technologies and adherence to regulations play key roles in ensuring the efficient and sustainable management of industrial wastewater. Considering the role of closed-loop supply chains in industrial wastewater collection, this paper presents a bi-objective mathematical model aimed at minimizing both the costs associated with surface wastewater collection and the environmental pollution from waste discharge. The model is solved using the multi-objective Grey Wolf Optimization algorithm. The results show that the model extends the network by including more vehicles and increasing the distances between locations. This optimal collection model ensures that wastewater is gathered from candidate sites by the vehicles within the network. Additionally, sensitivity analysis reveals that the most influential parameters on the model's objectives are the transportation cost per unit distance, the penalty for vehicle usage, and the revenue per kilogram of treated wastewater.